Committee tracker for Cornell College - Seubert, Walter (My University, 2010)
Committee membership is considered to be an important part of being on the faculty at Cornell College in Mount Vernon, Iowa. Approximately two thirds of the faculty members serve on a standing committee every year. The Committee on Committees is responsible for the lifecycle of all committees along with managing the election and nomination process for the standing committees. Managing the election and nomination process is a time consuming manual task from January through April every year. This manuscript describes the development of a web based application that enables the faculty at Cornell College to manage their committee system and to automate their voting system.
Keywords: Application software -- Development.; Web site development.; Committees.; Cornell College (Mount Vernon, Iowa) -- Faculty.